Building Data-Driven Organizations: A Theoretical Exploration of the Role of Leadership in Big Data Management - Abarca Pizarro, Sauken; Palacios Marques, Daniel (JOINETECH, 2025)
Problem: The adoption of Big Data and Business Intelligence is often limited by the lack of leadership with the necessary skills to manage the information provided by the data. This is compounded by the absence of an organization with an established data-driven culture. Objective: The objective of this study was to analyze how the role of leadership influences the development of a data-driven organizational culture and how this relates to Big Data management. Methodology: A qualitative approach with a theoretical-exploratory focus was used, based on a systematic literature review of high-impact databases such as Scopus and Web of Science regarding leadership, organizational culture, Big Data, and data culture. and decision-making processes published between 2015 and 2025. Results: The study identified four key drivers: data analysis, data democratization, data-driven leadership, and ethics in data-driven decision-making. Conclusion: Leadership is a fundamental factor in building a data-driven organizational culture. Its role is not limited to the adoption of technologies but extends to guiding cultural change processes that allow for the strategic and ethical use of Big Data for decision-making and the achievement of strategic objectives . Proper alignment between leadership, culture, and data management is required to build competitive organizations that are better prepared for digital transformation in dynamic environments.